Review of 'Interdisciplinary Perspectives on Aging in Nineteenth Century Culture' by Katharina Boehm, Anna Farkas, and Anne-Julia Zwierlein - Gilleard, Chris (Age, Culture, Humanities: An Interdisciplinary Journal, 2020)
---